2015
DOI: 10.1016/j.envres.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

The influence of obesity on blood mercury levels for U.S. non-pregnant adults and children: NHANES 2007–2010

Abstract: Background In animal studies obesity is associated with higher blood and tissue mercury concentrations; however human studies are lacking. Although the mechanism underlying this association is uncertain, obesity may alter the metabolism and distribution of methylmercury. Objectives We determined whether obesity influenced blood mercury levels, the majority of which was methylmercury, for U.S. non-pregnant adults (≥20 years) and children (2–19 years) after controlling for methylmercury intake through fish and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 40 publications
0
32
2
Order By: Relevance
“…In addition, blood mercury has been used in epidemiologic studies as a marker for mercury exposure in the general population [1324]. The geometric mean of the blood mercury concentration in this study was 3.42 µg/L.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, blood mercury has been used in epidemiologic studies as a marker for mercury exposure in the general population [1324]. The geometric mean of the blood mercury concentration in this study was 3.42 µg/L.…”
Section: Discussionmentioning
confidence: 67%
“… 7) There were a few studies reported a negative associations between mercury concentrations and BMI. 9) …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the number of studies conducted on the pediatric population, in this context, is limited. 8 9) …”
Section: Introductionmentioning
confidence: 99%
“…Dietary MeHg intake was low for most mothers, and therefore results were not necessarily applicable to populations ingesting more fish. Most mothers were overweight or obese, which possibly affected MeHg metabolism (Rothenberg et al 2015). However, aside from one genus ( Blautia ), there were no significant associations between obesity and gut microbiota, and there were no genera significant at the FDR of 20%.…”
Section: Discussionmentioning
confidence: 99%